Low pH induces amiloride-sensitive expression of leukemia inhibitory factor in endometrial cells - Miku OTSUGU; Ayumi MINE; Kurumi FUJIWARA; Ayako ICHIMURA; Keiji YAMAMOTO; Ryo TACHIHARA; Hideaki TOMURA (The Journal of Reproduction and Development)
An association has been reported between a lower pH in the uterus and an increased rate of implantation. How low pH regulates endometrial function is unclear. This study investigated the effect of low pH on the expression of leukemia inhibitory factor (LIF), which is crucial for implantation, in a human endometrial carcinoma cell line, rat endometrial stromal cells, and porcine endometrial cells. LIF mRNA expression was quantified by real-time PCR and protein expression was assessed using western blot analysis. LIF mRNA and protein expression increased at low pH in human endometrial carcinoma cells. Increased LIF mRNA expression was also detected at low pH in rat endometrial stromal and porcine endometrial cells, suggesting that low intrauterine pH may create favorable conditions for implantation and endometrial receptivity across species. The increase in LIF mRNA expression in the three cell types was attenuated by the addition of amiloride, indicating that low pH promotes the expression of LIF via amiloride-sensitive molecules in the endometrium.